1999
DOI: 10.1111/j.1749-6632.1999.tb07885.x
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphins: Novel Endogenous μ‐Opiate Receptor Agonists in Regions of High μ‐Opiate Receptor Density

Abstract: Endomorphin-1 (Tyr-Pro-Trp-Phe-NH2, EM-1) and endomorphin-2 (Tyr-Pro-Phe-Phe-NH2, EM-2) are peptides recently isolated from brain that show the highest affinity and selectivity for the mu (morphine) opiate receptor of all the known endogenous opioids. The endomorphins have potent analgesic and gastrointestinal effects. At the cellular level, they activate G-proteins (35S-GTP gamma-S binding) and inhibit calcium currents. Support for their role as endogenous ligands for the mu-opiate receptor includes their loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(71 citation statements)
references
References 29 publications
(48 reference statements)
2
67
0
2
Order By: Relevance
“…In the past decade the endomorphins EM-1 (Tyr-Pro-Trp-Phe-NH2) and EM-2 (TyrPro-Phe-Phe-NH2) were identified from bovine brain extracts as highly selective mu receptor agonists and appear to represent the endogenous ligands of the mu receptor [23]. While EM-1-like immunoreactivity is primarily restricted to brain, EM-2-like immunoreactivity is found primarily in the spinal cord and peripheral nervous system and may modulate spinal level pain signaling [24]. Despite the isolation of EM peptides from tissue however, the identity of the gene(s) encoding the precursor protein(s) from which the endomorphin peptides are derived has not been reported, which posed a challenge to gene transfer.…”
Section: Transgene-mediated Expression Of Opioid Peptidesmentioning
confidence: 99%
“…In the past decade the endomorphins EM-1 (Tyr-Pro-Trp-Phe-NH2) and EM-2 (TyrPro-Phe-Phe-NH2) were identified from bovine brain extracts as highly selective mu receptor agonists and appear to represent the endogenous ligands of the mu receptor [23]. While EM-1-like immunoreactivity is primarily restricted to brain, EM-2-like immunoreactivity is found primarily in the spinal cord and peripheral nervous system and may modulate spinal level pain signaling [24]. Despite the isolation of EM peptides from tissue however, the identity of the gene(s) encoding the precursor protein(s) from which the endomorphin peptides are derived has not been reported, which posed a challenge to gene transfer.…”
Section: Transgene-mediated Expression Of Opioid Peptidesmentioning
confidence: 99%
“…Radioimmunological and immunocytochemical analyses revealed that both endomorphins are densely distributed throughout the central nervous system, near neurons expressing the m-opioid receptors Zadina et al, 1999;Zadina, 2002). Endomorphins were found in the limbic system (septum, nucleus accumbens, amygdala), thalamic nuclei, locus coeruleus, and in the brain stem (Schreff et al, 1998;Martin-Schild et al, 1999;Zadina, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an endogenous tetrapeptide called endomorphin was isolated from bovine and human brain; endomorphin has at least equal affinity but greater specificity for the -opioid receptor than any other known synthetic or natural ligand (14,15). Two forms of endomorphin have been identified, of which endomorphin 1 is the most widely distributed and potent in controlling pain (16). The analgesic capacity of endomorphin 1 is generally equipotent with that of morphine but in some models is more effective than morphine and other -opioid receptor agonists (for review, see ref.…”
mentioning
confidence: 99%